The problem of man in the history of philosophy: a comparative analysis - Mustafayev , Azer Khoshbakht-oglu (Human in the Socio-Cultural Dimension, 2023)
Human is an entity of biosocial and psychological structure, unique and inimitable phenomenon, which enriched our material and spiritual world with philosophical deep ideas. In essence that living creature is a part of nature. Human is also a small and enormous life existing in it, like world of worlds. In addition, the smallest particle of a huge, of endless world is human. The issue of the essence of humanity in the combination within his natural and social qualities from the point of view of ethical norms is discussed in the article.